The impacts of climate change on ecosystem services in southern California - Underwood, Emma C.; Hollander, Allan D.; Safford, Hugh D.; Kim, John B.; Srivastava, Lorie; Drapek, Ray J. (Ecosystem services, 2019)
•Water runoff will change the most out of five services under future climates.•One-third of high biodiversity areas are threatened by high change in CWD.•Carbon storage in southern California has an estimated value of $7.5 billion.•Quantification of services under future climates can inform climate-smart strategies. Climate change is projected to impact ecosystem functioning, however its effect on the provision of ecosystem services is uncertain. This is particularly relevant on federal lands which harbor extensive tracts of natural vegetation. We assessed change in four ecosystem services (water runoff, groundwater recharge, carbon storage, and biodiversity) and one disservice (sediment export) in southern California between current and end-of-century (2070–2099). We used five general circulation models ranging from warmer wetter (CNRM-CM5, CCSM4) to hotter, marginally drier (IPSL-CM5A-LR) to hotter drier (FGOALS-g2, MIROC-ESM) under RCP8.5. We found greatest projected change in water runoff, from an increase of 127% under a warmer wetter GCM to a decrease of −60% under a hotter drier future. Carbon storage is projected to change the least, from an increase of 52% to a decrease of −31% across GCMs. We also determined that one-third of high biodiversity areas are threatened by high change in climatic water deficit. We estimated the current monetized annual value of sediment removal costs to be $172 million per year and the economic value of carbon storage as $7.5 billion. Understanding the impacts of climate change on ecosystem services can help develop climate-smart strategies for the sustainable management of natural resources.